Technology-Based Utilisation of Liquid Organic Fertiliser Derived from Herbal Medicine Waste and Rabbit Urine to Enhance Turmeric (Curcuma longa L.) Growth - Annisa Khoiriyah; Elea Nur Aziza; Geraldo Adinugra Rimartin (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The excessive use of synthetic fertilizers and pesticides in biopharmaceutical crop production has raised increasing concerns regarding environmental sustainability and food safety. This study investigated the potential of liquid organic fertilizer (LOF) derived from herbal medicine waste and rabbit urine as an alternative nutrient source for turmeric (Curcuma longa L.), focusing on plant growth, micronutrient uptake, and curcumin accumulation. A factorial randomized complete block design was implemented using varying concentrations of herbal medicine waste LOF (0–200 mL L?¹) and rabbit urine LOF (0–20 mL L?¹). Rhizome biomass, leaf iron (Fe) and boron (B) concentrations, and rhizome curcumin content were evaluated. The results demonstrated that moderate application rates of herbal medicine waste LOF (100 mL L?¹) combined with rabbit urine LOF (20 mL L?¹) effectively enhanced curcumin content without significantly increasing rhizome biomass. Elevated boron accumulation was observed at higher LOF concentrations. These findings highlight the potential of organic waste-derived LOF to improve turmeric quality while promoting sustainable and environmentally responsible cultivation practices. Contribution to Sustainable Development Goals (SDGs):SDG 2   : Zero Hunger SDG 12: Responsible Consumption and Production SDG 13: Climate ActionSDG 15: Life on Land